PENGARUH RADIUS PUNCH TERHADAP PENYIMPANGAN SPRINGBACK DALAM PEMBUATAN KEPALA SABUK - Widjaja, Hartono
Bending is a sheet metal forming that has been used widely in the forming industry. The process using a bending tool mounted on a press machines for mass production. During bending there is a reverse deformation called springback. This deformation is due to the elastic nature of material. Designer shall estimate the springback effect during bending tool design. Many factors can influence the springback effect such as plate thickness, plate materials, the speed of bending, bending tool construction, bending depth, radius and direction of the grain materials. Designer usually estimate the springback effect using literature data such as springback tabels, however for some cases the springback effect shall be corrected to obtain accurate results. This study discussed the effect of punch radius and orientation of the grains in the forming of steel plate with 1.8 mm thickness on the springback effect, under specified speed and depth of the defined bending to obtain the actual springback deviation. The result showed that the grain direction of steel plate under 3 mm thickness had no effect on springback deviation. The theoritical calculation method can only be applied to the product dimensional tolerances of approximately 0.2 mm and 2? of angle tolerance.